Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/suco.201300004
|View full text |Cite
|
Sign up to set email alerts
|

Non‐linear analysis of statically indeterminate SFRC columns

Abstract: The structural behaviour of steel fibre‐reinforced concrete (SFRC) has been studied using non‐linear finite element analysis (NLFEA) and ABAQUS software. An interesting feature of this work is the consideration of statically indeterminate SFRC columns. Most of the SFRC specimens studied in the literature are simply supported beams, and information on statically indeterminate columns is sparse. In addition, both axial and lateral loads were considered in order to allow for compression and flexural effects on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…The statically-indeterminate arrangement also allows for a study of the effect of fibres on strength, ductility as well as moment redistribution and formation of plastic hinges. The discussion presented herein is limited to the validation of the FE model against the experimental data, whilst the findings from an FE-based full parametric study carried out on these columns under both types of lateral loading can be found elsewhere [18,19]. For FE modelling purposes, the lateral load (whether monotonic or cyclic) was applied using a displacement-based method at point C in Fig.…”
Section: Statically-indeterminate Sfrc Columns Subjected To Combined mentioning
confidence: 99%
See 1 more Smart Citation
“…The statically-indeterminate arrangement also allows for a study of the effect of fibres on strength, ductility as well as moment redistribution and formation of plastic hinges. The discussion presented herein is limited to the validation of the FE model against the experimental data, whilst the findings from an FE-based full parametric study carried out on these columns under both types of lateral loading can be found elsewhere [18,19]. For FE modelling purposes, the lateral load (whether monotonic or cyclic) was applied using a displacement-based method at point C in Fig.…”
Section: Statically-indeterminate Sfrc Columns Subjected To Combined mentioning
confidence: 99%
“…The structural configurations considered herein include a wide range of SFRC specimens ranging from simply-supported SFRC beams with no conventional reinforcement to more complex (statically indeterminate, consisting of more than one structural elements and subjected to a combination of axial and lateral loading) SFRC structural configurations fully reinforced. It should be pointed out that although some of the case studies are presented herein for the first time, others have formed the basis for parametric investigations carried out recently assessing the effect of the fibre-content on RC structural responses [14][15][16][17][18][19][20]. The reason for presenting all the cases in the present article is to show the objectivity of the numerical model employed.…”
Section: Introductionmentioning
confidence: 95%
“…This allows the study of SFRC columns under both gravity and lateral seismic loads, with the reversed-cyclic nature of the latter modelled in the present study. The present paper is part of a research project, which has also examined SFRC columns under monotonic loads in its first phase with the findings reported elsewhere (Syed Mohsin 2012; Abbas et al 2014a).…”
Section: Introductionmentioning
confidence: 86%
“…The work is based on dynamic Nonlinear Finite Element Analysis (NLFEA), which was initially validated using exiting experimental data to ascertain its accuracy before the subsequent parametric studies were carried out. The work builds on previous NLFEA-based studies on various SFRC structural configurations subjected to both static monotonic and cyclic loading (the specimens covered a wide practical range from simply-supported beams to more complex structural systems characterised by a certain degree of static indeterminacy, such as continuous columns and beamcolumn sub-assemblages) [8][9][10][11]. Both previous and current studies utilize a material model for SFRC that is focused on realistically describing the fully brittle tensile behaviour of plain concrete as well as the contribution of steel fibres to the post-cracking response.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of steel fibres into the concrete mix can also lead to a reduction of transverse (i.e. shear) reinforcement such as beams, walls, joint regions [8][9][10][11]15] without compromising design codes [16,17] performance requirements for strength and ductility. The main benefit of such reduction is to alleviate reinforcement congestion due to dense arrangement and spacing of shear links in the critical regions of RC structures, as dictated in design codes such as the Eurrocode 8 for seismic-resistant design [17] in order to avoid brittle failure modes.…”
Section: Introductionmentioning
confidence: 99%